Successful Management of Patient with Sheehan's Syndrome Presenting with Psychosis and Catatonia - Nath, Santanu (Indian J Psychol Med, 2018)
Sheehan's syndrome is a neuroendocrine condition that manifests with symptoms of hypopituitarism. It mostly occurs as a complication of parturition due to severe postpartum hemorrhage compromising pituitary circulation. Reports of neuropsychiatric manifestations of Sheehan's syndrome are available with most cases describing psychosis. We report an interesting case of Sheehan's syndrome which presented with catatonia on a psychotic background and its successful management. The possible pathophysiological underpinnings for the causation of catatonia and psychosis in this condition are also discussed.